Ordinary fractional differential equations are in fact usual entire ordinary differential equations on time scales - Damasceno, Berenice Camargo [UNESP] (2014)
Despite the huge number of works considering fractional derivatives or derivatives on time scales some basic facts remain to be evaluated. Here we will be showing that the fractional derivative of monomials is in fact an entire derivative considered on an appropriate time scale.